2011
DOI: 10.4103/0975-5950.94471
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric facial injuries: It′s management

Abstract: Background:Facial injuries in children always present a challenge in respect of their diagnosis and management. Since these children are of a growing age every care should be taken so that later the overall growth pattern of the facial skeleton in these children is not jeopardized.Purpose:To access the most feasible method for the management of facial injuries in children without hampering the facial growth.Materials and Methods:Sixty child patients with facial trauma were selected randomly for this study. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 18 publications
3
22
0
7
Order By: Relevance
“…Conservative treatment in the form of long-term IMF with the aforementioned difficulties is not commonly applied in pediatric patients and is selectively used for 7e10 days following open reduction and internal fixation in cases of displaced non-condylar mandibular fractures (Pape et al, 1999;Zimmermann et al, 2006;Singh et al, 2011). Intraoral approach in MAFs, although difficult, has been proposed for the placement of an osteosynthesis plate even at the lower border of the mandible (Choi et al, 1995;Ellis, 2010b).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Conservative treatment in the form of long-term IMF with the aforementioned difficulties is not commonly applied in pediatric patients and is selectively used for 7e10 days following open reduction and internal fixation in cases of displaced non-condylar mandibular fractures (Pape et al, 1999;Zimmermann et al, 2006;Singh et al, 2011). Intraoral approach in MAFs, although difficult, has been proposed for the placement of an osteosynthesis plate even at the lower border of the mandible (Choi et al, 1995;Ellis, 2010b).…”
Section: Discussionmentioning
confidence: 97%
“…The incidence of MAFs in 12 years old children or less is low but increases with age (Thor en et al, 1992;Iida and Matsuya, 2002); it has been reported to range between 4 and 19.7% among all mandibular fractures (Thor en et al, 1992;Iida and Matsuya, 2002;Ferreira et al, 2005;Singh et al, 2011), whereas in adults, MAFs account for up to 30% of the total mandibular fractures (Chrcanovic, 2013). Findings of the present retrospective study (13%, 7/54 fracture sites) are in agreement with literature reports.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…9 Most condylar fractures are caused by indirect forces transmitted to the condyle from a blow elsewhere, 10 and traffic accidents, including bicycle crashes, are the main causes of these fractures in children. [11][12][13][14] With adequate molar support and the teeth in occlusion, little or no displacement is likely to be sustained, whereas the full force will be transmitted to the condyles if the mouth is wide open. 15 Ongoing controversy exists on the management of pediatric mandibular condylar fractures.…”
mentioning
confidence: 98%
“…Quanto aos tipos de fraturas faciais, este estudo encontrou que as fraturas nasais e do complexo zigomático-orbitário foram as mais frequentes. Alguns autores 14 reportaram ser os ossos nasais os mais acometidos, enquanto outros 3,8,18,19,21,27 afirmam que as fraturas mandibulares são as mais predominantes em indivíduos menores de 18 anos.…”
unclassified